2023
DOI: 10.3390/jcm12216884
|View full text |Cite
|
Sign up to set email alerts
|

Fear of COVID-19 Predicts Depression, Anxiety and Post-Traumatic Stress Disorders in Patients with Implantable Cardioverter Defibrillators and Is Mediated by Positive and Negative Affects—A Cross-Sectional Study

Marc Dörner,
Roland von Känel,
Aju P. Pazhenkottil
et al.

Abstract: The COVID-19 pandemic affected both the physical and mental health of the general population. People with cardiac diseases seem to be particularly vulnerable to the implications of the pandemic. However, studies on the mental health impact of the COVID-19 pandemic on people with implantable cardioverter defibrillator (ICDs) are lacking. Thus, we aimed to explore the level of fear of COVID-19 and the prevalence of anxiety, depression and post-traumatic stress disorder (PTSD) in ICD patients. Furthermore, we aim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…On the other hand, previous studies suggested worse emotional functioning and a reduced quality of life (QoL) after ICD implantation and ICD therapy [ 1 ]. Furthermore, 12% to 22% of ICD patients show signs of post-traumatic stress disorder (PTSD), depression, or anxiety [ 2 , 3 ], and these psychiatric symptoms and disorders are associated with increased mortality rates in those patients [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, previous studies suggested worse emotional functioning and a reduced quality of life (QoL) after ICD implantation and ICD therapy [ 1 ]. Furthermore, 12% to 22% of ICD patients show signs of post-traumatic stress disorder (PTSD), depression, or anxiety [ 2 , 3 ], and these psychiatric symptoms and disorders are associated with increased mortality rates in those patients [ 4 ].…”
Section: Introductionmentioning
confidence: 99%